Analisis Faktor-Faktor Yang Mempengaruhi KualitasAudit Pada Kantor Akuntan Publik Kota Surakarta Dan Semarang - Restiana, Ria; , Erma Setiawati, Ak, MM (2016)
This research purpose to analyze the effect of the independence, objectivity, knowledge, work experience, integrity, audit etic, and skepticism professional auditors on audit quality. The population used in this research is all of auditors who worked on the CPAs Office in Surakarta and Semarang city. This research use convenience nonrandom sampling in carry out sample selection. The data used in this research is primary data and data collection was performed using a questionnaire. The total sample collected as many as 35 questionnaire. Test statistic used is multiple linear regression test. The result of this research find type of the independence, objectivity, knowledge, work experience, audit etic, and skepticism professional auditors are related significant influence with audit quality. While integrity isn't relead significant influence with audit quality.